Tax Elements in Government Borrowing: the Nigerian case - Adewunmi, O.; NISER (Ibadan Nigerian Institute of Social and Economic Research, 1974)
The object of this paper is to examine how far government borrowing can be effectively distinguished from taxation, discuss how government policy overlaps into tax, discuss the significant of such overlapping with respect to the Nigerian public debt.
No. 91
osc 23/6/17
Loans
Keywords: Tax Administration